(untitled) (Journal of Social Sciences Review, 2022)
This research explores how corporate governance influences the connection between bank ownership and corporate output. To achieve this objective, the information for the years 2012 to 2021 of 60 listed non-financial corporations are collected from their yearly financial reports as well as from business record. Bank performance utilized as dependent variables, bank ownership is used as independent variable while corporate governance used as moderating variables. The moderating effect is investigated using regression analysis of corporate governance on the business performance and bank ownership relationship. The results revealed that bank ownership has significantly lower effect on performance, while The corporate governance has significantly favorable effect on company performs. Results also revealed that corporate governance positively moderate the association between bank ownership and business performance, as the indices of bank ownership become more substantial and favorable with the addition of moderating forces.